Determination of three‐dimensional muscle architectures: validation of the DTI‐based fiber tractography method by manual digitization. Issue 1 (16th May 2013) - Schenk, P.; Siebert, T.; Hiepe, P.; Güllmar, D.; Reichenbach, J. R.; Wick, C.; Blickhan, R.; Böl, M.
Abstract In the last decade, diffusion tensor imaging (DTI) has been used increasingly to investigate three‐dimensional (3D) muscle architectures. So far there is no study that has proved the validity of this method to determine fascicle lengths and pennation angles within a whole muscle. To verify the DTI method, fascicle lengths of m. soleus as well as their pennation angles have been measured using two different methods. First, the 3D muscle architecture was analyzed in vivo applying the DTI method with subsequent deterministic fiber tractography. In a second step, the muscle architecture of the same muscle was analyzed using a standard manual digitization system (MicroScribe MLX). Comparing both methods, we found differences for the median pennation angles (P < 0.001) but not for the median fascicle lengths (P = 0.216). Despite the statistical results, we conclude that the DTI method is appropriate to determine the global fiber orientation. The difference in median pennation angles determined with both methods is only about 1.2° (median pennation angle of MicroScribe: 9.7°; DTI: 8.5°) and probably has no practical relevance for muscle simulation studies. Determining fascicle lengths requires additional restriction and further development of the DTI method.